Comparative Clouds - Flaherty, Kyle (2020)
With the cloud industry still in its infancy, it is imperative to complete a thorough analysis of themajor competitors in this market. The research covered in this paper provides a comparativeanalysis of the main competitors in the cloud industry: Amazon Web Services, Google Cloud,and Microsoft Azure. The focus of this analysis will be structured around usability, performanceand cost. While the other competitors have their niche markets, the best overall cloud providerwas Amazon WebServices.